Diamonds in the marsh : a natural history of the diamondback terrapin - Brennessel, Barbara (Brandeis University Press, 2021)
"Synthesizing all known research on this remarkable animal, "Diamonds in the Marsh" is the first full-scale natural history of the diamondback terrapin. Focusing on the northern diamondback, Barbara Brennessel examines its evolution, physiology, adaptations, behavior, growth patterns, life span, genetic diversity, land use, reproduction, and early years"--